Formation and impact of hot spots on the performance of organic photovoltaic cells - Steim, Roland; Choulis, Stelios A.; Schilinsky, Pavel; Lemmer, Uli; Brabec, Christoph J. (My University, 2009)
The failure mechanisms of organic solar cells under reverse bias conditions were investigated. Localized inhomogenities, so-called “hot spots,” leading to increased leakage currents under reverse bias, were identified as the dominant origin for failure. The intensity of hot spots does increase with the duration under reverse bias voltage. Cells with a higher leakage current density (i.e., >100 µA/cm−2 at −1 V) have a significant higher probability for dominant failure, while devices with low leakage current densities show less degradation under reverse bias stressing.
Keywords: Current density; Failure analysis; Leakage currents; Organic compounds; Photovoltaic cells; Solar cells